Spatial distribution, source identification, and health risk assessment of fluoride in the drinking groundwater in the Sulin coal district, northern Anhui Province, China - Chunming Hao (IWA Publishing, 2021)
Previously, systematic studies of distribution, sources, and health risks of high F− groundwater used as a drinking-water source in the Sulin coal district, northern Anhui Province of China have not been carried out. In this study, 30 groundwater samples were collected in May 2019, and the data were analyzed using geographic information system, factor analysis, positive matrix factorization, and risk-based corrective action models. The results indicated that the F− concentration of the groundwater samples ranged from 0.16 to 2.06 mg/L, with a mean value of 1.10 mg/L. The F− concentrations of 53.33% of the groundwater samples exceeded China's maximum permissible limit for drinking water (1.00 mg/L). Quantificational source apportionment revealed that the weathering of F-bearing minerals is the main source (66.20%). Cation exchange (16.30%), agricultural activities (13.20%), and natural geological processes (4.30%) were the other sources of F−. The percentages of infants, children, teens, male adults, and female adults that face health risks due to excess F− intake were approximately 20.00%, 70.00%, 6.67%, 20.00%, and 10.00%, respectively. This research provided useful insights into the proper management of groundwater extraction to mitigate health problems associated with excessive F− intake. HIGHLIGHTS Quantificational source apportionment of F− in groundwater was carried out.; Health risk assessment of F− exposure was evaluated for individuals in different groups.; Spatial distribution was analyzed between low and high F− groundwaters in the Sulin coal district.;